Pertumbuhan dan Hasil 9 Galur Harapan Kedelai (Glycine max (L.) Merrill) pada Lahan Berpasir - Syaputra, Iwan; Suryati, Dotti; Djamilah, Djamilah (Akta Agrosia, 2017)
This research was conducted in Beringin Raya Sungai Hitam Village, Muara Bangkahulu Subdistrict, Bengkulu City from January to April 2016.  The research aims to compare the growth and yield of 9 lines of soybean expectation with 2 varieties of comparison (Tanggamus and Demas 1) on sandy land. The design used in this study was Completely Randomized Block Design (RAKL) using a single treatment factor of 11 soybean genotypes consisting of 9 lines of expectation (G4AB, G2BB, G1DB, 13 ED, 14 DD, 19 BE, 25 EC, G511H / Anj-2-10, and G511H / Anj-1-3) and 2 varieties of comparison (Tanggamus and Demas 1), each treatment was repeated four times to obtain 44 experimental units. Variables that significantly affect the F test at 5% level, followed by cluster analysis of Scott-Knott at 5% level. Of the 9 lines of expectation tested only 13 ED lines, 14 DD, and 25 EC had a number of comparable books comparable to the comparison varieties (Tanggamus and Demas 1). The comparative varieties had moderate flowering, deep harvest age, highest plant height, number of productive branches and the largest number of fertile books compared to the 9 tested lines. Density 13 ED, 14 DD, 25 EC has a number of pods of content comparable to the comparison varieties. The G511H / Anj-2-10 strain has more number of seeds per pod than the comparable strain / variety tested. The ED 13 line has a seed weight per plot proportional to the comparison varieties (Tanggamus and Demas 1), but is higher than the expected line of test. While the 19 BE strain has a weight of 100 seeds higher than the other strains / varieties tested